Degradation mechanism for high-temperature sliding wear in surface-modified In718 superalloy. Issue 1 (1st January 2018) - Thirugnanasambantham, KG.; Raju, Ramesh; Sankaramoorthy, T.; Velmurugan, P.; Kannagi, A.; Chaitanya Kishore Reddy, M.; Sai Koushik Chary, V.; Mustafa, M.A.; Ramesh Chandra, V.
Abstract: This technical paper deals with high-temperature dry sliding wear behavior and its mechanism of Al2 O3 –50TiO2 (A50T) coating on Inconel 718 alloy. The sliding wear behavior of the A50T coating on Inconel 718 alloy was investigated using a pin on disc equipment at 500°C with varying parameters like normal load and sliding velocity. Scanning Electron Microscope (SEM) features of worn samples reveal that ploughing, deep grooving and splat exfoliation are the dominant wear mechanisms of A50T coating at 10 N, while at 30 N, they are crack extension, crack deflection, crack bridging and splat exfoliation.